Muslim marriages, the South African state and the courts: between limbo, liberation, and the spaces for contestation in-between. Issue 1 (2nd January 2022) - Vahed, Goolam
ABSTRACT: A central feature of South Africa's legal system under white minority rule was the state's institutionalisation of racist structures and a distinct Christian bias in religious matters. Muslim marriages were not recognised because they permitted polygamy. Majority rule in 1994 resulted in the adoption of a new constitution that recognised non-Christian and 'non-European' beliefs and practices, and some Muslims lobbied for the legal recognition of Muslim marriages. While the new political context was sympathetic to accommodating multicultural practices, legislation stalled because of differences among Muslims over what constitutes Muslim Personal Law (MPL). This article focuses on debates in South Africa on state governance of Muslim family law and how, in the void created by the absence of legislation, the country's courts have seized the initiative through ex-post facto recognition of the consequences of Muslim marriages. South Africa thus represents a peculiar case of the courts recognising the consequences of Islamic marriages, even while Parliament has failed to write this into law. As such, South Africa provides a stark contrast to many other countries where there is acrimonious debate over legal pluralism and, in particular, accommodating MPL.